Developing molding technology module - study on effects of process parameter and equipment on mold defects for ball grid array (BGA) package - Leong, Hooi Shea
The aim of this project is to assert an optimize process parameter for a robust CGM transfer molding process in Ultra Fine Pitch (UFP) package. Project final result is a solution for encapsulating 35 micron wire bonded PBGA.